Nitrogen Absorption Rate in Kappaphycus alvarezii with a Longline System in the IMTA (Integrated MultiTrophic Aquaculture) Area at Ekas Bay - Muhaemi Muktiniati; Muhammad Junaidi; Bagus Dwi Hari Setyono (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
The rapid growth of the aquaculture sector can indirectly lead to the accumulation of unresolved aquaculture waste in the sea. The IMTA cultivation system is one of the innovations developed in aquaculture activities to overcome aquatic environmental problems, such as the accumulation of waste from feed used in aquaculture activities. The concept combines the cultivation of several species with different trophic levels, such as fish that are fed and combined with seaweed that can absorb inorganic materials in the water. The purpose of this study was to determine the level of nitrogen absorption in Kappaphycus alvarezii using a longline system in the IMTA area in the waters of Ekas Bay. This study used a Randomized Block Design (RAK) with 4 treatments and each treatment was divided into 4 groups (North, South, East, and West). The treatment given was planting seaweed at different depths, namely 50 cm, 100 cm, 150 cm, and 200 cm. The results showed that Kappaphycus alvarezii reared with an integrated cultivation system at different planting depths gave significantly different results in absolute weight growth with values ​​ranging from 120,31 grams – 195,58 grams and specific growth rates ranging from 2.67% - 4, 35%, but did not have a significant effect on the rate of nitrogen uptake in all treatments, but the highest absorption value was at a depth of 2 meters. So the researchers suggest the cultivation of Kappaphycus alvarezii at a depth of 2 meters in the waters of Ekas Bay, East Lombok with a longline system in the IMTA area.